Using Fun Thinkers Digital Media to Improve Understanding of the Benefits of Animals and Plants among Grade V Kolok Students - Ni Putu Lira Kusumadewi; I Gusti Ayu Tri Agustiana; Rendy Setyowahyudi (Indonesian Journal of Instruction, 2026)
The low level of conceptual understanding regarding the benefits of animals and plants among fifth-grade students is attributed to the dominance of teacher-centered, verbally oriented instructional methods, as well as the limited availability of interactive visual media based on the Indonesian Sign System (SIBI) for deaf students. This study aims to develop, validate, and evaluate the effectiveness of the Fun Thinkers Digital Media in enhancing conceptual understanding through a visual and interactive approach. This research employs a development method using the ADDIE model combined with a one-group pretest-posttest design. The subjects of the study include material experts, media experts, teachers, and students as primary users. Data were collected through expert validation questionnaires, user response questionnaires, and conceptual understanding tests. Data analysis techniques include qualitative descriptive analysis, validity testing, practicality assessment, normality testing, paired sample t-test, and N-Gain analysis. The results indicate that the developed media is highly valid, highly practical based on user responses, and effective in significantly improving students’ conceptual understanding. Therefore, the Fun Thinkers Digital Media facilitates active, visual, and inclusive learning and contributes to strengthening adaptive technology-based science learning practices for students with special needs.